A shish-kebab-like supramolecular polymer and its light-responsive self-assembly into nanofibers. Issue 10 (14th December 2020) - Chen, ChuanShuang; Huang, Pei; Pan, Hui; Qi, Meiwei; Xu, Qingsong; Dai, Haojie; Ji, Yi; Wang, Yuling; Yu, Chunyang; Zhou, YongFeng
Abstract : We report a shish-kebab-like supramolecular polymer (SKSP) and its light-responsive self-assembly into nanofibers. Abstract : This work reports on the synthesis and light-responsive self-assembly of a shish-kebab-like supramolecular polymer (SKSP). The SKSP has a linear alternating sequence structure and can self-assemble into nanofibers in water. In addition, the fibers can transform into spherical micelles under UV light due to the trans -to- cis isomerization of the azobenzene groups.